DEVELOPMENT OF A PERFORMANCE MONITORING SYSTEM TO OPTIMIZE PV BASED SOLAR ELECTRICITY GENERATION - A/L VIJAYA KUMAR, PRADEEP MENON (IRC, 2015)
Demand for electricity in Malaysia has seen a substantial hike in light of the nation’s rapid economic development in pursuit of achieving Vision 2020. The current method of generating electricity is through the use of conventional energy sources such as fossil fuels. However, consistent usage of fossil fuels has resulted in detrimental effects towards the environment besides the dampening amount of natural resources available globally. An alternative energy source that is capable of sustaining the demand is needed to ensure a sustainable future. Since its implementation through the Sustainable Energy Development Authority (SEDA), the Feed-in-Tariff (FiT) mechanism has established a total installed Photovoltaic (PV) capacity of 192 MW from 655 projects that are currently operational from the overall of 2628 approved projects in Malaysia.